PERAN ORANG TUA DALAM MENGEMBANGKAN KECERDASAN BERBAHASA PADA ANAK SPEECH DELAY USIA 4-5 TAHUN - Nurhabibah, Nurhabibah; Asiah, Nur; Istiarsyah, Istiarsyah (Universitas Jabal Ghafur, 2024)
Early childhood is the golden age, which is the most important period in a child's growth and development. Early childhood education must be designed to match their developmental stage. However, based on available data, around 5-10% of children worldwide experience speech or language delays at certain ages. Therefore, the role of parents is crucial in developing language intelligence in children with speech delays aged 4-5 years. The purpose of this study is to determine the role of parents in developing language intelligence in speech-delayed children aged 4-5 years. This study is a field study analyzed through qualitative descriptive methods. The data analysis technique involves three steps: data reduction, data presentation, and drawing conclusions. The respondents in this study were 3 parents and 3 children. Data were collected through observation and interviews. Based on the results of the study, the efforts made by parents include creating an environment that supports language development, providing quality time for verbal interaction, utilizing learning media, providing opportunities for social play, and seeking professional help. The conclusion of this study is that parents play a very important role in developing the language intelligence of children who experience speech delays. This study has significant implications both theoretically and practically. Theoretically, the findings contribute to a deeper understanding of the role of parents in developing language intelligence in children with speech delays.Keywords: Role of Parents, Language Intelligence, Speech Delay